Multidrug Combinations against SARS-CoV-2 Using GS-441524 or Ivermectin with Molnupiravir and/or Nirmatrelvir in Reconstituted Human Nasal Airway Epithelia - Denise Siegrist; Hulda R. Jonsdottir; Mendy Bouveret; Bernadett Boda; Samuel Constant; Olivier B. Engler (MDPI AG, 2024)
Background. The emergence, global spread, and persistence of SARS-CoV-2 resulted in an unprecedented need for effective antiviral drugs. Throughout the pandemic, various drug development and treatment strategies were adopted, including repurposing of antivirals designed for other viruses along with a multitude of other drugs with varying mechanisms of action (MoAs). Furthermore, multidrug treatment against COVID-19 is an ongoing topic and merits further investigation. Method/Objectives. We assessed the efficacy of multidrug treatment against SARS-CoV-2 in reconstituted human nasal epithelia, using combinations of molnupiravir and nirmatrelvir as a baseline, adding suboptimal concentrations of either GS-441524 or ivermectin, attempting to increase overall antiviral activity while lowering the overall therapeutic dose. Results. Nirmatrelvir combined with molnupiravir, GS-441524, or ivermectin at suboptimal concentrations show increased antiviral activity compared to single treatment. No triple combinations showed improved inhibition of SARS-CoV-2 replication beyond what was observed for double treatments. Conclusions. In general, we observed that the addition of a third compound is not beneficial for antiviral activity, while various double combinations exhibit increased antiviral activity over single treatment.